Routledge handbook of early Chinese history
1 online resource (546 pages)
Keywords: The study of early China has been radically transformed over the past fifty years by archaeological discoveries, including both textual and non-textual artefacts. Excavations of settlements and tombs have demonstrated that most people did not lead their lives in accordance with ritual canons, while previously unknown documents have shown that most received histories were written retrospectively by victors and present a correspondingly anachronistic perspective.